Evaluation of Adherence of Drug Promotional Literatures (DPLs) to World Health Organization Guidelines - Sultana, Anwara; Sorcar, Chandona; Karmaker, Mallika (Faridpur Medical College Journal, 2015)
There is limited mechanism to monitor the drug promotional campaign by pharmaceutical industries despite the fact that there is enough evidence of irrational pharmacotherapy increasingly encountered even in the developed countries. Unethical pharmaceutical promotional practice is a common cause of irrational pharmacotherapy which is a most common problem worldwide. Main objective of this study was to evaluate the medicinal promotional literatures provided by the pharmaceutical companies for accuracy, consistency and validity of the information presented in it, using World Health Organization (WHO) criteria for ethical medicinal drug promotion. Two hundred & fifty (n=250) literatures were collected randomly from selected doctors chambers in Barisal, Bangladesh. One hundred & thirty (130) of those literatures were excluded for being either duplicates, reminder literatures, promoting medical devices or cosmetics. The remaining (120) literatures were then screened to match their macro-informational contents against same advised in world health organization ethical criteria for medicinal drug promotion. The name of active constituent(s), content of active ingredient(s) per dosage form & brand name, were mentioned in 100% (n = 120) of promotional literatures, whereas dosage form were mentioned in 91.66% (n = 110), therapeutic indications were mentioned in 99.1% (n = 119) of literatures but informations on side effects mentioned in only 55.33% (n = 70), contraindications in 63.33 % (n = 76), precautions in 51.67% (n = 62) & references in 70 % (n = 84) of drug promotional literatures (DPLs). None of them mention anything about adjuvant. None of the promotional literatures fulfilled all the WHO criteria. Screened literatures were found to display poorly reliable and unbalanced medication information. Healthcare providers shall, accordingly, seek independent medicinal information sources, and not solely depend on commercial sources of medicinal information. Official regulators shall strictly define and mandate medication information contents in printed pharmaceutical promotional materials. Healthcare providers should, also, master the skills of appraising such promotional printed materials if rational medication use is to be achieved. Pharmaceutical industries did not follow the WHO guidelines while promoting their products, thus aiming to satisfying their commercial motive rather than fulfilling the educational aspect of promotion. Faridpur Med. Coll. J. 2014;9(2): 88-91